The place of emotions while inspecting schools: reflections of two Ofsted inspectors. (27th May 2017) - Elonga Mboyo, Jean Pierre
ABSTRACT: This article investigates the role of emotions of inspectors while inspecting schools as reported by inspectors themselves within an education context of increased accountability that arguably privileges rationality over emotions. The study is built on an emotion management framework that regards emotions not only as unavoidably natural and intimately linked to 'rational' judgements that people make, but also that such judgements are social constructions used to regulate expression of emotions. In-depth interview data of one retired and another, semi-retired Office for Standards in Education, inspectors were thematically analysed to assess the extent to which their emotions formed part of school inspections. In the absence of an officially sanctioned narrative of inspectors' emotions during inspections, two kinds of self-prescribed emotions emerged as key findings: emotions for accountability, to which inspectors gave expression, and emotions for improvement, that they suppressed. For an inspection body that needs to ensure both accountability and improvement of schools to justify its viability, these research claims open up a new area of discussion that should lead to a review of inspection body's stance on emotions and individual inspectors' self-reflections on the moral as well as professional obligation to pursue both emotions for accountability and improvement.